Online learning study in divorce cases management: A case study at “Pejabat Agama Islam Kuantan” - Asar, Abdul Karim; Aziman, Abdullah (Universiti Malaysia Sarawak (UNIMAS), 2019)
Divorce cases among Muslims in Malaysia is still in a high ratio statistics. This issue significantly affects the social progress of the nation. In many cases, the divorcee and their children are struggling mentally and emotionally in adapting with the new environment after the divorce. Many studies have been conducted about the divorce in Malaysia; most seems to focus on the factors that lead to the divorce; others focus on the processes of the divorce and ways to prevent it. Less study found to focus on post-divorce help, let it be alone to discuss about the post-divorce support centre. Therefore, a new proposed online divorce support management system has been proposed by the researchers to overcome the problems. The system highlights the potential of online learning as one of the proposed mechanism in managing divorce cases. Based on some interviews conducted at Kuantan Islamic Religious Office [Pejabat Agama Islam Kuantan], the concept of online learning is very novel and practical to be implemented by the religious office.